The Effect of Earnings per Share (EPS), Return on Equity (ROE), Debt-to-Equity Ratio (DER), and Total Asset Turnover (TATO) on Stock Returns (Using Company Age and Firm Size as Control Variables) - Okta Viani Puspitasari; Pristin Primasari; Johannes Maysan Damanik (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of Earnings Per Share (EPS), Return on Equity (ROE), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on stock returns in basic and chemical manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study is based on signaling theory and firm value theory to explain the relationship between financial performance and investment decisions. A quantitative method was used using secondary data from annual financial reports. The study sample consisted of 16 companies selected through purposive sampling, with a total of 80 observations. Data analysis used multiple linear regression. The results show that EPS, ROE, DER, and TATO have a positive and significant effect on stock returns. This finding indicates that profitability, capital structure, and asset efficiency are important factors in investment decision-making.